Flexible ceramic tile and preparation method thereof
By combining the polysiloxane prepolymer with self-crosslinked acrylic acid, an inorganic hybrid material is formed and used in combination with polymer emulsion, the problem of poor water resistance of soft ceramic tiles is solved, and its stability in humid environments is significantly improved.
Patent Information
- Application Number
- CN202411593432.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-25
AI Technical Summary
Soft ceramic tiles have poor water resistance, especially when they are easily whitened in humid environments or when soaked in rainwater, which limits their application scope.
The polysiloxane prepolymer is used to combine with self-crosslinked acrylic acid, and the water resistance of soft ceramic tiles is improved through the formation of inorganic hybrid materials and combined with polymer emulsions.
It significantly improves the water resistance of soft ceramic tiles, reduces color changes in humid environments, and enhances its use stability under high humidity conditions.
Smart Images

Figure HR2SVVDF71HECLIC9WE9AWPA4PFSVDQKNOKI2FPT
Abstract
Description
Technical Field
[0001] The present application relates to the field of building decoration, and more specifically, to a soft tile and a preparation method thereof. Background Art
[0002] Ceramic tiles, as a man-made building material widely used in building decoration and wall protection, are highly favored for their corrosion resistance, easy cleaning and beautiful appearance. However, ceramic tiles are rigid facing tiles. Changes in ambient temperature can easily cause ceramic tiles to expand or contract, causing fatigue in the bonding interface, leading to ceramic tiles falling off the wall. Once ceramic tiles fall off, they will pose a serious threat to pedestrians and vehicles downstairs. Therefore, ceramic tiles have been banned as exterior wall finishing materials for high-rise buildings regardless of region.
[0003] With the advancement of technology and the diversification of consumer demand, a kind of soft ceramic tile that can replace ceramic tiles for building exterior wall decoration has emerged. Soft ceramic tiles not only have the decorative effect of ceramic tile walls, but also have the characteristics of thin thickness, light weight, and deformation ability. They can effectively reduce the weight of the building exterior wall decoration and the load of the decoration layer, and improve the safety of the exterior wall decoration layer.
[0004] However, there are certain performance shortcomings in the use of soft ceramic tiles, such as poor water resistance. This is because most of the current flexible facing tiles use acrylic emulsion as an organic binder, and the water absorption rate of acrylic emulsion is relatively high, which causes the flexible facing tiles to easily turn white in a humid environment or after being soaked in rainwater, which greatly restricts the application of flexible facing tiles. Summary of the invention
[0005] The invention object of this application is to improve the water resistance of soft tiles.
[0006] In order to achieve the above-mentioned invention object, the present application provides a soft ceramic tile and a preparation method thereof, adopting the following technical solution: In a first aspect, the present application provides a soft ceramic tile, comprising, by weight: 60-80 parts of polymer emulsion; 40-50 parts of polysiloxane prepolymer; 10-20 parts of self-crosslinking acrylic acid; 10-20 parts of curing agent; 15-25 parts of plasticizer; Thickener 3-5 parts; Filler 600-700 parts; 100-150 parts of water; The polysiloxane prepolymer is prepared from silica sol, alkoxysilane and a capping agent.
[0007] Furthermore, the polysiloxane prepolymer is prepared from silica sol, alkoxysilane and end-capping agent in a weight ratio of 1:(1-2):(0.5-1).
[0008] Furthermore, the alkoxysilane includes one or more of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane.
[0009] Furthermore, the alkoxysilane is composed of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane in a weight ratio of 1:(0.2-0.4):(0.6-0.8):(0.1-0.3).
[0010] Furthermore, the polymer emulsion is one or more of pure acrylic emulsion, silicone acrylic emulsion and acrylic emulsion modified by organic silicon compound with hydroxyl carbon number ≥6.
[0011] Furthermore, the organic silicon compound having 6 or more carbon atoms in the hydroxyl group refers to hydroxytriethoxysilane having 6 or more carbon atoms in the hydroxyl group.
[0012] Furthermore, the plasticizer is one or more of a citrate plasticizer, a polyester plasticizer and a benzoate plasticizer.
[0013] Furthermore, the curing agent is toluene diisocyanate and / or diphenylmethane diisocyanate.
[0014] Furthermore, the thickener is a cellulose ether thickener and / or a polyurethane thickener.
[0015] In a second aspect, the present application provides a method for preparing the soft ceramic tile described in the first aspect, comprising the following steps: S1, after mixing alkoxysilane and end-capping agent, adding silica sol, keeping warm for reaction, to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer and the self-crosslinking acrylic acid, and reacting them at a temperature keeping the mixture warm; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold, drying and forming at 80-90° C. to obtain the soft ceramic tile.
[0016] In summary, this application has the following beneficial effects: The polysiloxane prepolymer of the present application is an inorganic component, which is organically modified by self-cross-linking acrylic acid to obtain an inorganic hybrid material with silicon dioxide as the core and a carbon chain as the shell, which has good rigidity and toughness. In addition, since the polysiloxane prepolymer contains a large amount of hydroxyl groups, it is used in combination with a polymer emulsion to greatly improve the water resistance of soft tiles. DETAILED DESCRIPTION
[0017] The technical scheme and effects of the present application are further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the invention, rather than to limit the invention.
[0018] Example 1 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0019] The soft ceramic tile is prepared by the following steps: S1, after mixing alkoxysilane and end-capping agent, add silica sol, keep warm and react for 2 hours at 50°C and 30rpm to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer with the self-crosslinking acrylic acid, and keeping the mixture for reaction at 40°C and 30 rpm for 2 h; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold and drying and forming at 80°C to obtain the soft ceramic tile.
[0020] Wherein, the weight ratio of silica sol, alkoxysilane and capping agent is 1:1:0.5; The alkoxysilane is a mixture of methyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 1:1; The capping agent is trimethylmethoxysilane; The silica sol is a nano silica sol with a particle size of 20-40 nm; The polymer emulsion is BASF 7015 pure acrylic emulsion; The curing agent is toluene diisocyanate; The plasticizer is tri-n-butyl citrate plasticizer; The thickener is hydroxyethyl cellulose; The filler is 60-100 mesh colored quartz sand.
[0021] Example 2 A soft tile, wherein all raw materials for preparing the soft tile include 65 kg of polymer emulsion, 43 kg of polysiloxane prepolymer, 13 kg of self-crosslinking acrylic acid, 13 kg of curing agent, 18 kg of plasticizer, 3.5 kg of thickener, 625 kg of filler and 115 kg of water.
[0022] The soft ceramic tile is prepared by the following steps: S1, after mixing alkoxysilane and end-capping agent, add silica sol, keep warm and react for 2 hours at 50°C and 30rpm to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer with the self-crosslinking acrylic acid, and keeping the mixture for reaction at 40°C and 30 rpm for 2 h; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold and drying and forming at 80°C to obtain the soft ceramic tile.
[0023] Wherein, the weight ratio of silica sol, alkoxysilane and capping agent is 1:1:0.5; The alkoxysilane is a mixture of methyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 1:1; The capping agent is trimethylmethoxysilane; The silica sol is a nano silica sol with a particle size of 20-40 nm; The polymer emulsion is BASF 7015 pure acrylic emulsion; The curing agent is toluene diisocyanate; The plasticizer is tri-n-butyl citrate plasticizer; The thickener is hydroxyethyl cellulose; The filler is 60-100 mesh colored quartz sand.
[0024] Example 3 A soft tile. All raw materials for preparing the soft tile include 70 kg of polymer emulsion, 45 kg of polysiloxane prepolymer, 15 kg of self-crosslinking acrylic acid, 15 kg of curing agent, 20 kg of plasticizer, 4 kg of thickener, 650 kg of filler and 125 kg of water.
[0025] The soft ceramic tile is prepared by the following steps: S1, after mixing alkoxysilane and end-capping agent, add silica sol, keep warm and react for 2 hours at 50°C and 30rpm to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer with the self-crosslinking acrylic acid, and keeping the mixture for reaction at 40°C and 30 rpm for 2 h; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold and drying and forming at 80°C to obtain the soft ceramic tile.
[0026] Wherein, the weight ratio of silica sol, alkoxysilane and capping agent is 1:1:0.5; The alkoxysilane is a mixture of methyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 1:1; The capping agent is trimethylmethoxysilane; The silica sol is a nano silica sol with a particle size of 20-40 nm; The polymer emulsion is BASF 7015 pure acrylic emulsion; The curing agent is toluene diisocyanate; The plasticizer is tri-n-butyl citrate plasticizer; The thickener is hydroxyethyl cellulose; The filler is 60-100 mesh colored quartz sand.
[0027] Example 4 A soft tile, wherein all raw materials for preparing the soft tile include 75 kg of polymer emulsion, 47 kg of polysiloxane prepolymer, 17 kg of self-crosslinking acrylic acid, 17 kg of curing agent, 22 kg of plasticizer, 4.5 kg of thickener, 675 kg of filler and 135 kg of water.
[0028] The soft ceramic tile is prepared by the following steps: S1, after mixing alkoxysilane and end-capping agent, add silica sol, keep warm and react for 2 hours at 50°C and 30rpm to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer with the self-crosslinking acrylic acid, and keeping the mixture for reaction at 40°C and 30 rpm for 2 h; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold and drying and forming at 80°C to obtain the soft ceramic tile.
[0029] Wherein, the weight ratio of silica sol, alkoxysilane and capping agent is 1:1:0.5; The alkoxysilane is a mixture of methyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 1:1; The capping agent is trimethylmethoxysilane; The silica sol is a nano silica sol with a particle size of 20-40 nm; The polymer emulsion is BASF 7015 pure acrylic emulsion; The curing agent is toluene diisocyanate; The plasticizer is tri-n-butyl citrate plasticizer; The thickener is hydroxyethyl cellulose; The filler is 60-100 mesh colored quartz sand.
[0030] Example 5 A soft tile. All raw materials for preparing the soft tile include 80 kg of polymer emulsion, 50 kg of polysiloxane prepolymer, 20 kg of self-crosslinking acrylic acid, 20 kg of curing agent, 25 kg of plasticizer, 5 kg of thickener, 700 kg of filler and 150 kg of water.
[0031] The soft ceramic tile is prepared by the following steps: S1, after mixing alkoxysilane and end-capping agent, add silica sol, keep warm and react for 2 hours at 50°C and 30rpm to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer with the self-crosslinking acrylic acid, and keeping the mixture for reaction at 40°C and 30 rpm for 2 h; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold and drying and forming at 80°C to obtain the soft ceramic tile.
[0032] Wherein, the weight ratio of silica sol, alkoxysilane and capping agent is 1:1:0.5; The alkoxysilane is a mixture of methyltrimethoxysilane and ethyl orthosilicate in a weight ratio of 1:1; The capping agent is trimethylmethoxysilane; The silica sol is a nano silica sol with a particle size of 20-40 nm; The polymer emulsion is BASF 7015 pure acrylic emulsion; The curing agent is toluene diisocyanate; The plasticizer is tri-n-butyl citrate plasticizer; The thickener is hydroxyethyl cellulose; The filler is 60-100 mesh colored quartz sand.
[0033] Example 6 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0034] The difference from Example 1 is that in the preparation process of the polysiloxane prepolymer, the weight ratio of the silica sol, the alkoxysilane and the capping agent is 1:1.5:0.7.
[0035] Example 7 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0036] The difference from Example 1 is that in the preparation process of the polysiloxane prepolymer, the weight ratio of the silica sol, the alkoxysilane and the capping agent is 1:2:1.
[0037] Example 8 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0038] The difference from Example 1 is that the alkoxysilane is a mixture of methyltrimethoxysilane, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane in a weight ratio of 1:1:1.
[0039] Example 9 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0040] The difference from Example 1 is that the alkoxysilane is a mixture of methyltrimethoxysilane, ethyl orthosilicate and methacryloxypropyltrimethoxysilane in a weight ratio of 1:1:1.
[0041] Example 10 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0042] The difference from Example 1 is that the alkoxysilane is a mixture of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane in a weight ratio of 1:0.2:0.6:0.1.
[0043] Embodiment 11 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0044] The difference from Example 1 is that the alkoxysilane is a mixture of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane in a weight ratio of 1:0.3:0.7:0.2.
[0045] Example 12 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0046] The difference from Example 1 is that the alkoxysilane is a mixture of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane in a weight ratio of 1:0.4:0.8:0.3.
[0047] Embodiment 13 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0048] The difference from Example 1 is that the silica sol is a mixture of nano silica sol with a particle size of 20-40 nm and nano silica sol with a particle size of 100-120 nm in a weight ratio of 1:1.
[0049] Embodiment 14 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0050] The difference from Example 1 is that the silica sol is a nano silica sol with a particle size of 100-120 nm.
[0051] Embodiment 15 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0052] The difference from Example 1 is that the polymer emulsion is silicone acrylic emulsion DP-510.
[0053] Example 16 A soft tile. All raw materials for preparing the soft tile include 60 kg of polymer emulsion, 40 kg of polysiloxane prepolymer, 10 kg of self-crosslinking acrylic acid, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0054] The difference from Example 1 is that the polymer emulsion is octyltriethoxysilane-modified acrylic emulsion.
[0055] Comparative Example 1 A soft tile, wherein all raw materials for preparing the soft tile include 60 kg of polymer emulsion, 10 kg of curing agent, 15 kg of plasticizer, 3 kg of thickener, 600 kg of filler and 100 kg of water.
[0056] The soft ceramic tile is prepared by the following steps: The polymer emulsion, curing agent, plasticizer, thickener, filler and water are mixed and stirred, poured into a mold and dried at 80°C to obtain the soft ceramic tile.
[0057] Among them, the polymer emulsion is BASF 7015 pure acrylic emulsion; The curing agent is toluene diisocyanate; The plasticizer is tri-n-butyl citrate plasticizer; The thickener is hydroxyethyl cellulose; The filler is 60-100 mesh colored quartz sand.
[0058] Performance Testing The soft tiles prepared in Examples 1 to 16 and Comparative Example 1 were tested.
[0059] According to the preparation methods in the embodiments and comparative examples, soft ceramic tile samples with a specification of 50 mm*240 mm were prepared.
[0060] The detection method is as follows: Water resistance test: Put the prepared soft tile sample into 20±3℃ water, with the water covering the upper surface of the soft tile by 30mm. Soak for 24 hours to observe whether the color changes. Compare with the unsoaked soft tile and record the color change.
[0061] Water absorption test: select 5 samples from each group, weigh each sample to an accuracy of 0.1g, and then place them in 20±3℃ water, with the water covering the upper surface of the soft tile by 30mm. Take them out after soaking for 24 hours, wipe off the visible water on the surface with a wet towel, weigh them after soaking for 24 hours, and wipe off the visible water on the surface with a wet towel. Weigh them after soaking for 48 hours, and calculate the water absorption after soaking for 24 hours and 48 hours respectively. The average value of the 5 samples is taken as the water absorption.
[0062] Softness test: refer to the method specified in JG / T311-2011 Flexible facing tiles, place the sample with its front side facing outwards, close to a cylinder with a diameter of 200mm, and slowly bend it to observe whether there are cracks on the surface of the sample.
[0063] The test results are as follows: From the above results, it can be seen that the polysiloxane prepolymer of the present application is an inorganic component, which is organically modified by self-cross-linking acrylic acid to obtain an inorganic hybrid material with silica as the core and a carbon chain as the shell, which has good rigidity and toughness. Moreover, since the polysiloxane prepolymer contains a large amount of hydroxyl groups, it is used in combination with the polymer emulsion to greatly improve the water resistance of the soft ceramic tiles.
[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A soft tile, characterized in that: In parts by weight, including: 60-80 parts of polymer emulsion; 40-50 parts of polysiloxane prepolymer; 10-20 parts of self-crosslinking acrylic acid; 10-20 parts of curing agent; 15-25 parts of plasticizer; Thickener 3-5 parts; Filler 600-700 parts; 100-150 parts of water; The polysiloxane prepolymer is prepared from silica sol, alkoxysilane and a capping agent.
2. The soft ceramic tile according to claim 1, characterized in that: The polysiloxane prepolymer is prepared from silica sol, alkoxysilane and end-capping agent in a weight ratio of 1:(1-2):(0.5-1).
3. The soft tile according to claim 2, characterized in that: The alkoxysilane includes one or more of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane.
4. The soft ceramic tile according to claim 1, characterized in that: The alkoxysilane is composed of methyltrimethoxysilane, ethyl orthosilicate, methacryloxypropyltrimethoxysilane and phenyltrimethoxysilane in a weight ratio of 1:(0.2-0.4):(0.6-0.8):(0.1-0.3).
5. The soft ceramic tile according to claim 1, characterized in that: The polymer emulsion is one or more of pure acrylic emulsion, silicone acrylic emulsion and acrylic emulsion modified by organic silicon compound with hydroxyl carbon number ≥6.
6. The soft ceramic tile according to claim 5, characterized in that: The organic silicon compound having hydroxyl carbon atoms of ≥6 refers to hydroxytriethoxysilane having hydroxyl carbon atoms of ≥6.
7. The soft ceramic tile according to claim 1, characterized in that: The plasticizer is one or more of a citrate plasticizer, a polyester plasticizer and a benzoate plasticizer.
8. The soft ceramic tile according to claim 1, characterized in that: The curing agent is toluene diisocyanate and / or diphenylmethane diisocyanate.
9. The soft ceramic tile according to claim 1, characterized in that: The thickener is a cellulose ether thickener and / or a polyurethane thickener.
10. The method for preparing soft ceramic tiles according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, after mixing alkoxysilane and end-capping agent, adding silica sol, keeping warm for reaction, to obtain polysiloxane prepolymer; S2, mixing the polysiloxane prepolymer and the self-crosslinking acrylic acid, and reacting them at a temperature keeping the mixture warm; S3, adding polymer emulsion, curing agent, plasticizer, thickener, filler and water, mixing and stirring, pouring into a mold, drying and forming at 80-90° C. to obtain the soft ceramic tile.